Psychological preparation for radiotherapy on a patient with a brain tumor: case report - Sierra-Murguía, Mariana Alejandra; González-Alcocer, Lucía del Carmen; Delgado-Vargas, Salvador; Mazatán-Orozco, Regina (Psicooncología, 2024)
Introduction: Meningiomas represent 27% of brain tumors in adults. Radiotherapy is one of the most frequent treatments for CNS tumors, in which high radiation doses destroy cancer cell’s DNA in order to stop their multiplication or to slow their growth. Patient’s inmovilization is necessary in this treatment, so he has to be attached to treatment bed with a thermogenic mask. This inmovilization has represented significant anxiety prior and during treatment, it can also represent a trigger for stress, fears, physical symptoms, pain and even claustrophobia. Considering this, a psychological preparation is suggested before radiotherapy. It is suggested o include clear information before and during simulation, and to identify patients with high levels of anxiety, and to deliver cognitive and behavioral strategies to regulate it. Aim: to describe a case report of a psychological preparation for CNS radiotherapy. Method: A case of a 61 year old woman who was referred to psycho-oncology service with the aim of psychological preparation for CNS radiation. The reason this patient was referred was to avoid sedation during treatment due to high levels of anxiety. Psychologic preparation consisted in two sessions that included psychoeducational, systematic desensibilization and diaphragmatic breathing strategies. Results: Subjective anxiety report was reduced with psychologic preparation, and the patient finished 25 sessions of radiotherapy without sedation. Conclusion: Psychological preparation in this patient was efective in anxiety reduction. It is important to design randomized controled studies in order to know the effectiveness of these strategies.